CRUSTAL ELECTRIC CONDUCTIVITY STRUCTURE FOR WUDALIANCHI VOLCANIC CLUSTER IN THE HEILONGJIANG PROVINCE, CHINA - Zhan Y.; Zhao G.Z.; Wang J.J.; Xiao Q.B.; Tang J.; Rokityansky I. (My University, 2006)
We have made reprocessing to the data from seven magnetotelluric survey profiles, which were carried out at the Wudalianchi volcanic cluster of Helongjiang Province in 1997. A detailed analysis is performed to describe features of parameters such as real and virtual induction vectors and apparent resisitivity at all measurement sites. The two-dimensional NLCG method is used to inverse data for the three nearly EW trending profiles to reveal the electric conductivity structure beneath this area. The results shows that in the Wudalianchi volcanoes, the scale of the volcanic chain along Bijiashan-Laoheshan-Huoshaoshan mountains is obviously larger than that of the Gelaqiu volcanic chain in the north and south, and of the Jiaodebu chain in the east and west. Volcanic activity of the Bijiashan-Laoheshan-Huoshaoshan mountains seems to migrate from southwest to northeast. Below this volcanic chain, there exists a rivet-shaped block at depths about several hundred in to 20km, which strikes in NNE, looking like wide in the upper and northern parts, and narrow in the lower and southern parts. With increasing depth, the values of its resistivity decreases gradually from over 1000Ωm to about 1Ωm. Beneath the depth 20km, this block tends to extend downward, probably through crust and to upper mantle. At depths about 4 ~ 8km, there are bodies of low resistivity on the both eastern and western sides of the Huoshaoshan, Laoheshan, and Bijiashan mountains. In combination with other observations such as S wave velocity, small earthquakes, and geothermal measurements, it is inferred that there may be a magma system in the crust beneath the volcanic chain along the Bijiashan-Laoheshan-Huoshaoshan mountains, of which the solidification degree varies with increasing depth.
Keywords: CONCRETION MAGMA; ELECTRIC CONDUCTIVITY STRUCTURE; WUDALIANCHI VOLCANIC CLUSTER